Research on Monitoring and Early Warning of the Mine Backfill System Based on Blockchain Technology - Xuebin Qin; Jingtao Huo; Jing Zhang; Lang Liu; Pai Wang; Lihong Dong (Applied Sciences, 2022)
At present, the mine filling system is a mostly automated operation process, and it has many problems, such as centralized data storage and low safety performance. Aiming at solving the above problems, this paper proposes a mine filling overlimit warning system based on blockchain to achieve the functions of an equipment operation overlimit warning, data storage, and data retrieval. Firstly, the original data model is trained based on transfer learning to obtain the overlimit early warning model and predict the overlimit of equipment operation. Then, the interplanetary file system (IPFS) storage device is used to store the running data and overlimit data, and the corresponding file identifier CID is stored on the blockchain. At the same time, alliance chain technology is used to allow administrators and users to retrieve data based on credentials to ensure the privacy of the data retrieval process. System experiments and analysis evaluations show that the combination of blockchain and IPFS to store monitoring data can effectively save storage space and improve the efficiency of storage and retrieval. The application of an overlimit early warning model can optimize the mine filling process and prolong the operational life of system equipment.